USING OF THE SERVICE LANDS IN URBAN CENTERS OF AFAK DISTRICT - حسن جبر, وفاء (Journal of College of Education, 2019)
The district of Afak is one of the four districts of the province of Qadisiyah (Diwaniyah - Shamiya - Afak - Hamzah) and is located in the central part of Iraq, 175 km southwest of the capital Baghdad, which is a natural unit within the region of the plain sediment and limit the judiciary from the north-west province of Babylon and from the east and north-east Wasit province and from the south-east province of Dhi Qar and the west and north-west district of Diwaniya and south-west of Hamzah district, and consists of Afak administrative district of the judiciary and three aspects of ( Al Badair - Sumer - Nefer). The study aims to:1) Study the geographical distribution of community services for urban centers in Afak district from a geographical point of view based on determining the levels of spatial relationship between the services and institutions provided by the side and the degree of functional and local interaction with the population on the other hand.2) Study the planning efficiency performed by the service organizations and the extent of success of their planning and administrative role in the success of the integrated urban plans and the establishment of services, taking into consideration the amount of individual services.3) To harness geographic ideas in improving the quality of community services (educational, health, religious, leisure) in urban areas in particular and the possibility of achieving distributive justice between the size of the population and the areas of production and service delivery.The study concluded:Afak district enjoys a distinct geographic location because it is a link between the center and south of Iraq, as well as the availability of water resources represented by rivers and irrigation tables that can be invested and make them tourist areas that attract all the world's population, especially the study area from the archaeological areas dating back to Akkadian and Sumerian covenants.The high rates of population growth in the district of Afak for the period (1997-2007) in excess of the expansion of services, which put pressure on services.The large number of kindergartens and the lack of a system of geographical distribution for the institutions of primary and secondary education.The large disparity in the number of health institutions between the center of the judiciary and its subdivisions, where the General Hospital Afak provides health services to all residents of the judiciary neighboring regions.Recreational services (parks and parks) did not receive any care and interest in the elimination of Afak, despite the lungs that breathe residents of Afak district.The list of sources:The BooksAbu Ayna, Fathi Mohammed, Population Geography, 3, Dar al-Nahhah al-Arabiya, Beirut, 1986.Al-Shammari, Imad Mutair, Population Geography Foundations and Applications, 1, Dar Osama Publishing and Distribution, Amman, 2012.Al-Shammari, Wafa Abdul-Jabbar et al., Development of Archaeological Tourism in Qadisiyah Governorate, 1, Al-Raed Press, Najaf, 2009.Al-Tayef, D. Bashir Ibrahim and others, city services study in geographical development, i 1, civil institution of the book, Lebanon, 2009.Hiney, Gerry Fares, Geography of Cities, Dar Al-Safa Publishing and Distribution, Amman, 2010.Reputation, D. Moussa, Geography of Population, I 2, Alexandria, 2009.Ghalab, Mohamed El Sayed, Mohamed Sobhi Abdel Hakim, Demographics and Geography, II, The Anglo-Egyptian Library, Cairo, 1967.Second: Researches & Thesis:Arakan, Haider Hamza, Forms of the Surface of the Land in Afak District of Qadisiyah Governorate, unpublished Master Thesis, Department of Geography, Faculty of Basic Education, Mustansiriya University, 2017. Al-Badairi, Ali Hussein Odeh, Geographical Demographic Analysis of the Population Hierarchy in Qadisiyah Governorate (1987-2007), Unpublished Master Thesis, Department of Geography, Faculty of Arts, Qadisiyah University, 2011. Hassan, Haidar Majid, Social Participation in the Evaluation of Basic Urban Schemes, unpublished Master Thesis, Higher Institute of Urban and Regional Planning, 2009.The journals: Shandal, Abdul Kadhim, The Reality of Vocational Education in Qadisiyah Governorate for the Years (1970-1997) Qadisiyah Journal, Volume 6, 2001.Abdul Salam, Dr. Emad, Encyclopedia of Iraq Civilization, Part X, Center for Revival Heritage, Baghdad, 1985.Alwan, Walid Abdul Amir, Encyclopedia of Tourism and Antiquities of Iraq, House of Books and Documents, Baghdad, 2013.Ayyad, Adnan Anad, Mohamed Atelih Mahod Al-Malki, Population Distribution and Change in Dhi Qar Governorate (1977-1997), Adab Dhi Qar Magazine, Issue 5, Volume 2, 2012.Kazar, Latif Hashim, Indicators of Concentration of the Population of Muthanna Province, Journal of the Professor, No. 204, Volume I, 2013.Matar, Salim and Others, Encyclopedia of Iraqi Cities, Center for Arab Nation Studies, Baghdad, 2005. Departments of Government Directorate of Education Afak, Division of Research and Development, unpublished data, 2017.Diwaniyah Health Department, Special Clinics Division, unpublished data, 2016.Directorate of the Municipality of Qadaafak, Division of Gardens and Agriculture, Planning and Follow-up, unpublished data, 2008.